Ökonomische Aspekte bei der Versorgung von Patient*innen mit neuen oralen Tumortherapeutika: Erkenntnisse aus der AMBORA-Studie - Dürr, Pauline; Schlichtig, Katja; Krebs, Sabine; Schramm, Anja; Schötz, Lukas; Fromm, Martin; Dörje, Frank (Zeitschrift für Evidenz, Fortbildung und Qualitat im Gesundheitswesen, 2022)
Introduction: The number of prescriptions and costs of oral anticancer drugs are increasing. Therapy discontinuation due to, for example, side effects, progression, or death, often lead to medication wastage. While evidence exists for the economic value of wasted injectable chemotherapeutics, there is a lack of data for oral anticancer drugs in Germany. Methods: The multicenter AMBORA trial investigated 202 patients, who had been newly started on new oral anticancer drugs, over 12 weeks and analyzed the outpatient prescription data of patients who discontinued treatment. The amount of medicines wasted and their costs were determined using the pharmacy retail price. Defined daily doses and prescription data from AOK Bayern, a German statutory health care insurance company, were used to extrapolate these costs. Results: Within 12 weeks, 24.8 % of the AMBORA patients discontinued oral anticancer treatment (50 of 202). Prescription data of 34 patients were evaluable. In total, 1,693 tablets/capsules with a value of 112,212 euros were wasted. The approximate extrapolation to the prescription volume of AOK Bayern resulted in an estimated wastage of 3.49 million euros in 12 weeks. Discussion: Medication wastage due to discontinuation of new oral anticancer drug therapy leads to a considerable financial burden. Regarding rising prescription numbers and therapy costs in oncology, measures to reduce wastage of oral anticancer drugs should be initiated. Conclusion: Clinical pharmacological / pharmaceutical care including medication reconciliation and review, side effect management and patient counseling to optimize adherence and medication intake behavior, contributes to a reduction of therapy discontinuations, thereby reducing drug wastage. To further reduce drug wastage small (initiation) packages, which are currently not always available for an economic prescription, play an important role. The practice of partial prescription fills, which is already practiced internationally, should also be further discussed in Germany.
CRIS-Team Scopus Importer:2022-03-11
Keywords: Drug costs; Economics; Medication wastage; Oral anticancer agents; Treatment discontinuation